Planting conditions can enhance the bioactivity of mulberry by affecting its composition - Bai, Huixin; Jiang, Shanfeng; Liu, Jincai; Tian, Ye; Zheng, Xiaohui; Wang, Siwang; Xie, Yanhua; Li, Yao; Jia, Pu (Frontiers in Plant Science, 2023)
Mulberry (Morus alba L.) has a special significance in the history of agriculture and economic plant cultivation. Mulberry has strong environmental adaptability, a wide planting range, and abundant output. It is not only an important resource for silkworm breeding but also a raw ingredient for various foods and has great potential for the development of biological resources. The bioactivities of mulberry in different planting areas are not the same, which is an obstacle to the development of mulberry. This study collected information on the planting conditions of mulberry branches in 12 planting areas, such as altitude, temperature difference, and precipitation. A comparison of the levels of 12 constituents of mulberry branches from mulberry grown in different planting areas was then made. An in vitro model was used to study the bioactivities of mulberry branches in the 12 planting areas, and mathematical analysis was used to explain the possible reasons for the differences in the composition and bioactivities of mulberry branches in different planting areas. After studying mulberry samples from 12 planting areas in China, it was found that a small temperature difference could affect the antiapoptotic effect of mulberry branch on microvascular endothelial cells by changing the levels and proportions of rutin, hyperoside, and morusin. Adequate irrigation can promote the antioxidation of the mulberry branch on microvascular endothelial cells by changing the levels and proportions of scopoletin and quercitrin. The results of the analysis of planting conditions and the levels of active constituents and their correlation with bioactivities support the improvement of mulberry planting conditions and have great significance in the rational development of mulberry resources. This is the first time that a mathematical analysis method was used to analyze the effects of planting conditions on mulberry biological activity.